Extremum Seeking Control for Truck Drag Reduction - Whidborne, James F.; Garry, Kevin (Cranfield University, 2018)
MATLAB/Simulink codes for "Extremum Seeking Control for Truck Drag Reduction" G Papageorgiou, J Barden, J Whidborne, K Garry 12th UKACC International Conference on Control Sheffield, UK, 5th - 7th September 2018 Videos: converge.mp4 - shows ESC controller convergence with Speed controller reference, Vr=24 m/s Initial deflector height limits, deltaH=1.16 Gradient and wind speed are set to zero
Keywords: Extremum Seeking Control'; 'Truck Drag Reduction'; 'flow control'; 'Aerodynamics (excl. Hypersonic Aerodynamics)'; 'Automotive Mechatronics'; 'Automation and Control Engineering'